(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
This paper will explore the matter of wrongful birth and wrongful life suits, focusing on how it has been addressed by the courts (both from a comparative and from a national point of view) and on its impact on some of the main values involved, especially on women’s autonomy and on equal dignity of disabled people.